The validity and reliability of the functional rating index for evaluating low back pain in athletes - Naghdi, S.; Nakhostin Ansari, N.; Yazdanpanah, M.; Feise, R. J.; Fakhari, Z. (Scandinavian Journal of Medicine & Science in Sports, 2015)
The purpose of the present study was to determine the reliability and validity of the Functional Rating Index (FRI) for athletes with low back pain (LBP). In this cross-sectional and prospective cohort study, the validated Persian FRI (PFRI) was tested in 100 athletes with LBP and 50 healthy athletes. From the athletes with LBP, data were recollected among 50 athletes with a 7-day interval to examine test-retest reliability. The content validity was excellent, and the athletes with LBP responded to all items with no floor or ceiling effects. The discriminative validity was supported by a statistically significant difference in PFRI total scores between the athletes with LBP and healthy athletes. The concurrent criterion validity was good (rho = 0.72). The construct, convergent validity was good (r = 0.83). The internal consistency reliability estimate was high (Cronbach's a = 0.90). Factor analysis demonstrated a single-factor structure with an explained variance of 52.22%. The test-retest reliability was excellent, indicated by an ICCagreement of 0.97, and the agreement observed in the Bland and Altman plot demonstrated no systematic bias. It is concluded that the PFRI has excellent psychometric properties for assessing athletes with LBP.